Swiss National Bank: Is the recent loss a threat to monetary policy? A research note - Vanessa Kämpf; Georg Stadtmann; Lilli Zimmermann (Journal of Central Banking Theory and Practice, 2024)
The Swiss National Bank (SNB) has announced it will refrain from profit distribution in 2022 owing to the accumulation of a huge financial loss. In this paper we examine key determinants of the SNB's loss and shed light on its implications to monetary policy pursuit. In particular, we show that different accounting principles yield different results concerning the equity position of a central bank's balance sheet, yet not affecting the ability to run monetary policy.
Keywords: E05; G15; 330; Swiss National Bank; central bank; monetary policy; intervention